Application of Blended Learning in Physical Education Learning for Students' Critical Thinking in High Schools - OOM ROHMAH; RESHANDI NUGRAHA; RIZKY AKBAR HERDIANSYAH; RIORA GIBRAN TABRANI (Universitas Pendidikan Indonesia (UPI), 2022)
Introduction: Students' critical thinking skills must be improved even though during the Covid-19 pandemic, learning is done at home. They have a blended learning model as an alternative learning model that can be applied in schools during the Covid-19 pandemic. Purpose: This study aims to determine the effect of applying the blended learning model in physical education learning on the critical thinking of high school class students. This research was conducted in one of the senior high schools in the city of Bandung. Â Methods: Applying a quantitative descriptive approach with a survey method. The total population used is 249, with a sample of 156 respondents. The sampling technique used is simple random sampling. The instrument used is a Questionnaire Physical Activity Questionnaire for Adolescents, which adopts from previous research that has been tested for validity with a value of -0.010 - 0.0506 and reliability of 0.682 - 0.745 so that it is declared valid and reliable, used to measure physical strength activity according to by age and distributed via Google Form with data analysis techniques assisted by Microsoft Excel. Â Results: The research method used in this study was an actual experiment. By cluster random sampling, two research groups were selected in class XI, divided into two, namely the experimental group and the control group, which both amounted to 35 peopleâ€”a total of 16 meetings. The experimental and control groups received treatment, the experimental groups received the blended learning model treatment, and the control group received the conventional learning model treatment. Instruments were given to pretest and posttest. In this study, the instrument to measure students' critical thinking skills was adopted from the Watson-Glaser Critical Thinking Appraisal, which consists of five components including 1) inference, 2) recognition of assumptions, 3) deduction, 4) interpretation, and 5) evaluation of arguments. Conclusions: The results of data analysis using the SPSS version 28 test paired sample t-test obtained a p-value of the experimental group of 0.000 0.05, which means that the blended learning model can significantly improve students' critical thinking, while the p-value in the control group is 0.000 0.05 which means that the application of conventional learning models has a significant effect on increasing students' critical thinking skills. The results of the independent sample T-test showed that the p-value = 0.000 0.05, which means that there is a significant difference in the average between the experimental group and the control group, with the difference in the post-test average value of the experimental being 16.75 more significant than the control group. Blended learning has a more significant effect on improving students' critical thinking skills than conventional learning models. A blended learning model can be applied to improve one of the life skills in the 21st century, namely critical thinking for high school students.